2022
DOI: 10.3164/jcbn.21-145
|View full text |Cite
|
Sign up to set email alerts
|

Linked color imaging effectively detects the endoscopic atrophic border in transnasal endoscopy

Abstract: In oral endoscopy, linked color imaging (LCI) detects atrophic border and gastric mucosal diseases better than white light imaging (WLI), but its usefulness in transnasal endoscopy has not been fully investigated. Here, we retrospectively compared WLI and LCI using the L*a*b* color space in images from 57 patients aged ≥20 years who had undergone transnasal endoscopy as part of a health check-up from May 2016 to January 2017. We measured color differences at the atrophic/non-atrophic and fundic/pyloric mucosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, the major and serious disadvantages of first- and second-generation UTE that were used for screening include poor image quality and lower diagnostic accuracy of EGC 29 . It was therefore difficult to distinguish different structures and contrast of color between the EGC and background gastric mucosa, but the recently developed high-definition third-generation UTE has markedly improved image quality compared with standard-definition second-generation UTE and oral endoscopy 15 19 , 25 . Sugita et al 18 reported that the ability of third-generation UTE to detect EGC was significantly higher than that of second-generation UTE (accuracy: 80.8% vs. 71.6%, P = 0.017; sensitivity: 94.9% vs. 76.5%, P < 0.001; positive predictive value, 76.2% vs. 55.3%, P < 0.001; and negative predictive value, 94.1% vs. 73.5%, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the major and serious disadvantages of first- and second-generation UTE that were used for screening include poor image quality and lower diagnostic accuracy of EGC 29 . It was therefore difficult to distinguish different structures and contrast of color between the EGC and background gastric mucosa, but the recently developed high-definition third-generation UTE has markedly improved image quality compared with standard-definition second-generation UTE and oral endoscopy 15 19 , 25 . Sugita et al 18 reported that the ability of third-generation UTE to detect EGC was significantly higher than that of second-generation UTE (accuracy: 80.8% vs. 71.6%, P = 0.017; sensitivity: 94.9% vs. 76.5%, P < 0.001; positive predictive value, 76.2% vs. 55.3%, P < 0.001; and negative predictive value, 94.1% vs. 73.5%, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Previous first- and second-generation UTEs had low resolution, and it was hence difficult to distinguish various structures and contrasts of color between the EGC and the background gastric mucosa. However, the recently developed high-definition third-generation UTE has improved resolution, and it is becoming possible to detect EGCs and to make accurate endoscopic diagnoses using not only WLI but also IEE 15 19 . Nevertheless, the gold standard for screening EGD is still WLI.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with current H. pylori infection and patients in whom H. pylori had been eradicated, color differences at the atrophic border observed by LCI were 21.58 ± 6.97 and 27.34 ± 10.32, respectively, compared with 14.42 ± 5.95 ( P = 0.004) and 17.9 ± 8.48 ( P < 0.001), respectively, as observed by WLI. We concluded that color differences were larger when using LCI 36 …”
Section: Advancement Of Transnasal Endoscopymentioning
confidence: 99%
“…We concluded that color differences were larger when using LCI. 36 Figure 3 The patient was a woman in her 60s. Transnasal ultrathin esophagogastroduodenoscopy (EG530N; Fujifilm) showed early gastric cancer in the lessor curvature in lower body of the stomach (type 0-IIa, tub1, pT1a [M], UL[-], ly0, v0).…”
Section: Case Presentationmentioning
confidence: 99%
“…Second, although endoscopic evaluation using IEE increases the detection rate of atrophy, intestinal metaplasia, and gastric cancer, not all cases used IEE for endoscopic evaluation. 29,36 In this study, endoscopic evaluation was performed with IEE at 78.7% (208/328) of all endoscopies and with indigo carmine at 63.4% (208/328). Third, we had no data on pathological evaluation of gastric condition.…”
Section: M Itati O N Smentioning
confidence: 99%